2012
DOI: 10.1093/oxrep/grs038
|View full text |Cite
|
Sign up to set email alerts
|

The ECB's non-standard monetary policy measures: the role of institutional factors and financial structure

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(33 citation statements)
references
References 15 publications
1
30
0
2
Order By: Relevance
“…Draghi's July 2012 statement and the introduction of the Outright Monetary Transactions (OMT) program in September 2012 were among the key steps that stabilized the looming threats on Eurozone integrity. The OMT program allowed the unlimited purchase of sovereign securities in stressed countries, reducing sharply GIIPS sovereign spreads [29]. 10 The ECB policies in 2012 took place before putting in place a transparent structure that would buffer the balance sheet of the agencies funding these bailouts.…”
Section: Discussionmentioning
confidence: 99%
“…Draghi's July 2012 statement and the introduction of the Outright Monetary Transactions (OMT) program in September 2012 were among the key steps that stabilized the looming threats on Eurozone integrity. The OMT program allowed the unlimited purchase of sovereign securities in stressed countries, reducing sharply GIIPS sovereign spreads [29]. 10 The ECB policies in 2012 took place before putting in place a transparent structure that would buffer the balance sheet of the agencies funding these bailouts.…”
Section: Discussionmentioning
confidence: 99%
“…This would safeguard against 20 See Masera (2009;Cour-Thimann andWinkler (2012). It should be observed that the U.S. addressed this problem by means of the Troubled Asset Relief Program (TARP), aimed at restoring financial confidence and stability and restarting economic growth.…”
Section: Figure 4 -Equilibrium Expected Returns In a "Trade-off Model"mentioning
confidence: 99%
“…Temporary swap lines were established with other central banks, primarily to address the mounting pressure in short-term US dollar funding markets. As a result, the tensions in the short-term segment of the euro area money market abated considerably" (Cour-Thimann & Winkler 2012). "Following the bankruptcy of Lehman Brothers on 15 September 2008, the uncertainty about the financial health of major banks worldwide led to a collapse in financial activity.…”
Section: The Transformation Of Monetary Policymentioning
confidence: 99%
“…The evidence available suggests that the non-standard measures taken in October 2008 have been instrumental in stabilizing the financial system and the economy, as well as in ensuring price stability (Cour-Thimann & Winkler 2012). "In early 2010 the euro area sovereign debt crisis began with acute market expectations about a possible Greek sovereign default, with a risk of impact on Ireland, Portugal, and even Spain and Italy.…”
Section: The Transformation Of Monetary Policymentioning
confidence: 99%